Testimonium de Auditu Witness: Comparison of Maṣlāhah in the Settlement of Syiqāq in the Religious Court of the Border Regions - Nofiardi, Nofiardi (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2023)
Witness examination is one of the trial procedures required to resolve cases before the Religious Courts. According to the regulations, witnesses must provide information directly related to their testimony that they actually have seen, heard, or experienced the case. The issue is that some of the witnesses introduced were unaware of the testimony they provided and only learned about it from the litigants. How can the Religious Courts in the border area, which is the Minang region, resolve the syiqāq case from a maṣlāhah perspective, and what are the solutions that can be implemented to bring about a positive outcome in the syiqāq case when the witness's closest family does not have knowledge about the case in person? Comparing these two court products in terms of maṣlāhah is an intriguing analysis. Using a comparative approach to the two cases, this study conducted a fundamental analysis of the literature. The results demonstrated that distinct assemblies evaluated the presence of these witnesses in relation to the issued decisions. Some of the panels regarded the testimony in this case as insufficient evidence, so they denied the requested divorce despite the family's ongoing disputes (syiqāq). In petition cases with the same witness issue, however, the tribunal deemed the evidence to be sufficient to grant the requests.